2021
DOI: 10.1186/s12888-021-03509-3
|View full text |Cite
|
Sign up to set email alerts
|

Associations of serum cystatin C with depressive symptoms and suicidal ideation in major depressive disorder

Abstract: Background Individuals with major depressive disorder (MDD) have high suicidal ideation. There is evidence that serum cystatin C (Cys C) may be involved in the pathophysiology of MDD. The present study aimed to investigate Cys C concentration in patients with MDD and clarify its possible association with depressive symptoms and suicidal ideation. Methods An online cross-sectional survey of 159 patients diagnosed with MDD was conducted. Serum Cys C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…History of mental illness was the strongest risk factor associated with SI [ 31 ]. Our study finding that demoralization and depression could accelerate SI in cancer patients, which is consistent with Wu and Sun [ 27 , 32 ]. Although the clinical manifestations of demoralization and depression are similar, there are differences between the two diagnoses.…”
Section: Discussionsupporting
confidence: 92%
“…History of mental illness was the strongest risk factor associated with SI [ 31 ]. Our study finding that demoralization and depression could accelerate SI in cancer patients, which is consistent with Wu and Sun [ 27 , 32 ]. Although the clinical manifestations of demoralization and depression are similar, there are differences between the two diagnoses.…”
Section: Discussionsupporting
confidence: 92%
“…We found that DNAmADM, DNAmPAI-1, and DNAmTIMP-1 levels were increased and DNAmCystatinC is likely to increase in patients with untreated MDD, suggesting that these epigenetic markers may be useful in understanding the pathophysiology of MDD and as potential biomarkers. Previous studies have also reported an association between increased levels of DNAmCystatinC and MDD 21 , 23 , as well as higher serum cystatin C levels in individuals with depression 44 46 . Cystatin C inhibits endogenous cysteine protease activity, is an established marker of kidney function, and involved in immunomodulation and inflammation 47 , 48 .…”
Section: Discussionmentioning
confidence: 77%
“…These results suggest that these relationships are likely to be of clinical significance and warrants further study. Although high cystatin C levels have been linked with major depressive disorder, 37 no studies, to the best of our knowledge, have demonstrated an association between cystatin C and bipolar disorder. Levels of Cystatin C, a natural inhibitor of cysteine proteases, are typically used clinically to assess kidney function.…”
Section: Discussionmentioning
confidence: 81%